2015
DOI: 10.1073/pnas.1501769112
|View full text |Cite
|
Sign up to set email alerts
|

Role for RNA:DNA hybrids in origin-independent replication priming in a eukaryotic system

Abstract: DNA replication initiates at defined replication origins along eukaryotic chromosomes, ensuring complete genome duplication within a single S-phase. A key feature of replication origins is their ability to control the onset of DNA synthesis mediated by DNA polymerase-α and its intrinsic RNA primase activity. Here, we describe a novel origin-independent replication process that is mediated by transcription. RNA polymerase I transcription constraints lead to persistent RNA:DNA hybrids (R-loops) that prime replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 80 publications
(77 reference statements)
4
94
3
Order By: Relevance
“…These alleles were particularly intriguing because previous studies have shown that the majority of Rad52-GFP foci seen in RNase H mutants co-localize with the nucleolus. This suggested that the lethal events seen in rnh1D rnh201D top1D cells were rDNA-specific (Stuckey et al, 2015). Consistent with these findings, we observed efficient repair of a DSB on chromosome V by BIR and NHEJ in top1D and rnh1D rnh201D cells.…”
Section: Rna Polymerase I Is a Barrier To The Repair Of Hybrid-inducesupporting
confidence: 89%
See 4 more Smart Citations
“…These alleles were particularly intriguing because previous studies have shown that the majority of Rad52-GFP foci seen in RNase H mutants co-localize with the nucleolus. This suggested that the lethal events seen in rnh1D rnh201D top1D cells were rDNA-specific (Stuckey et al, 2015). Consistent with these findings, we observed efficient repair of a DSB on chromosome V by BIR and NHEJ in top1D and rnh1D rnh201D cells.…”
Section: Rna Polymerase I Is a Barrier To The Repair Of Hybrid-inducesupporting
confidence: 89%
“…Consistent with the notion that persistent DNA damage uniquely affects the double mutants, the growth of the double mutant, but not either of the single mutants, was dramatically impaired by the deletion of RAD52 ( Figure 1B). Previous characterization of the double mutant also reported elevated foci and Rad52-dependent growth (Stuckey et al, 2015;Lazzaro et al, 2012). Thus, by measures of Rad52-GFP foci and Rad52-dependent growth, cells lacking RNase H1 and H2 had a larger fraction of persistent R-loop induced damage than wild-type cells or cells lacking only one of the RNases H. This persistent damage could have arisen from increased R-loop induced damage and/or an inability to efficiently repair that damage.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations